Novel multiphoton intravital imaging enables real-time study of Helicobacter pylori interaction with neutrophils and macrophages in the mouse stomach - Ishikawa-Ankerhold, Hellen; Busch, Benjamin; Bader, Almke; Maier-Begandt, Daniela; Dionisio, Flavio; Namineni, Sukumar; Vladymyrov, Mykhailo; Harrison, Ute; Heuvel, Dominic van den; Tomas, Lukas; Walzog, Barbara; Massberg, Steffen; et al. (PLoS pathogens, 2024)
Helicobacter pylori (H. pylori) is a bacterial pathogen that exclusively colonizes the human gastric mucosa and can cause persistent infection. In this process, H. pylori employs various strategies to avoid recognition by the human immune system. These range from passive defense strategies (e.g., altered LPS or flagellin structures) that prevent recognition by pattern recognition receptors (PRRs) to more active approaches, such as inhibition of IL-2 secretion and proliferation of T cells via VacA. Despite the growing evidence that H. pylori actively manipulates the human immune system for its own benefit, the direct interaction of H. pylori with immune cells in situ is poorly studied. Here, we present a novel intravital imaging model of the murine stomach gastric mucosa and show for the first time the in situ recruitment of neutrophils during infection and a direct H. pylori-macrophage interaction. For this purpose, we applied multiphoton intravital microscopy adapted with live drift correction software (VivoFollow) on LysM-eGFP and CX3CR1-eGFP reporter mice strains in which specific subsets of leukocytes are fluorescently labeled. Multiphoton microscopy is proving to be an excellent tool for characterizing interactions between immune cells and pathogens in vivo.
Gesehen am 03.04.2025